2016
DOI: 10.21608/scumj.2016.44182
|View full text |Cite
|
Sign up to set email alerts
|

The Unmet Need for Contraception among Married Women in Nefesha Village in Ismailia

Abstract: Background: Unintended pregnancy is a worldwide problem which affects women, their families, and society. Aim: to determine the prevalence and determinant of the unmet need of family planning among married women in the child bearing period in Nefesha Village in Ismailia. Subjects and methods: This cross-sectional study was conducted on 823 married women in reproductive age (15-49 years). Data were collected through a structured interview questionnaire sheet. The sample size was estimated according to the stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…19 a demographic health survey comparative reports 34 in developing countries in 2014 revealed that unmet need to family planning was higher among younger women (age 15-19) than older women (age 20-24) as reported by Macquarrie and Dejenu et al 20,21 This might be younger age groups have no satisfactory data with respect to contraception and comprehensive education of sexuality. Regarding women working status, in accordance with our findings, El-Masry et al 7 reported that working women were significantly higher among the unmet need group while it was disagreed with previous studies in Egypt by El-Gendy et al and Mohamed 9,10 and also by Vohra et al in India who concluded that there was no significant difference between both groups regarding their working status. 22 In general, working women had greater chances to engage with the outside world, which exposed her to the others' ideas, experiences, and rumors about possible side effects of contraceptive methods hence avoid using them.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…19 a demographic health survey comparative reports 34 in developing countries in 2014 revealed that unmet need to family planning was higher among younger women (age 15-19) than older women (age 20-24) as reported by Macquarrie and Dejenu et al 20,21 This might be younger age groups have no satisfactory data with respect to contraception and comprehensive education of sexuality. Regarding women working status, in accordance with our findings, El-Masry et al 7 reported that working women were significantly higher among the unmet need group while it was disagreed with previous studies in Egypt by El-Gendy et al and Mohamed 9,10 and also by Vohra et al in India who concluded that there was no significant difference between both groups regarding their working status. 22 In general, working women had greater chances to engage with the outside world, which exposed her to the others' ideas, experiences, and rumors about possible side effects of contraceptive methods hence avoid using them.…”
Section: Discussionsupporting
confidence: 75%
“…However, the current rate of unmet need was lower than rates reported in previous studies conducted in other Egyptian Governorates by El-Gendy et al in Banha, Mohamed in Ismailia and Braghi et al in Assuit where the unmet need were (30%, 15.7% and 24.5%; respectively). 9,10,11 The discrepancy in Assuit may be because of lower levels of contraceptive usage and higher fertility rates in Upper Egypt. In opposite to the current result the unmet need for family planning among rural married women was 26.1% in Ethiopia as reported by Solomon et al 17 The most frequent reasons for nonuse of contraception among females with unmet needs were fear of side effects (43.5%), then infrequent sex (23%), lactation (20.5%), old age (17.9%).These results run with that reported by El-Masry et al which found that more than half of women with unmet needs perceived that they were not at risk of pregnancy due to (infrequent sex 27.3%, subfecundity 11.4%, older age 6.8%) while 25% recorded their fear of side effects and 15.9% reported resistance from husbands, religious prohibition was reported by only 6.8%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sultan et al [ 20 ], in their study which was conducted in an underprivileged district in Eastern Cairo, showed that 7.4% of studied women were having an unmet need for family planning. In another survey of married women (2016) in Nefesha Village in Ismailia, the reported prevalence of unmet need for family planning was 15.7% [ 21 ]. This percentage was 11.2% in a third study conducted at Mansoura governorate during 2015-2016 [ 22 ].…”
Section: Discussionmentioning
confidence: 99%